Differential Object Marking in Romance The third wave - Kabatek, Johannes; Obrist, Philipp; Wall, Albert (De Gruyter, 2021)
After a "first wave" of traditional studies on prepositional accusatives and a "second wave" exploring the typological dimensions of Differential Object Marking in Bossong's footsteps, a new line of research is currently introducing new methods, deepening the level of analysis, and offering new perspectives on the issue. This volume presents 11 innovative, original contributions representative of this "third wave" of studies on DOM in Romance.